If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
-5/3 = (1/5)*x-(1/2) // - (1/5)*x-(1/2)
1/2-((1/5)*x)-5/3 = 0
(-1/5)*x-5/3+1/2 = 0
-1/5*x-7/6 = 0 // + 7/6
-1/5*x = 7/6 // : -1/5
x = 7/6/(-1/5)
x = -35/6
x = -35/6
| 24=3(9-2) | | (9x-4)(4x-9)=0 | | -369=9(5x+9) | | 0=1.8*x+32 | | y-4=1/3(x-2) | | 9m+5n-3m+9n= | | 24=3(-2-2) | | b=1/5ht | | X^2-5x+20=6x-4 | | -3x+26=-7 | | 10r+100s+50t= | | 4÷1/3 | | 1/3-9/15 | | (49w^12)^1/2 | | -2-4(2-4x)=-10-2x | | (49w12^12)^1/2 | | 24=3(10-2) | | 24=3(-1-2) | | y-65=-10x+60 | | 30=-30n^2+6 | | 7/8-1/8= | | 1/3x-8=12 | | 30=-30n+6 | | 2a+7=-(2+a) | | -1/2(t=9)=53/4t=3/8t | | -6x+6(4x+6)=-116 | | H=11.50 | | 0.59x+1800=1.6x | | 30x+10-10d+4m= | | H=2.25 | | 4x-9=3x+4x | | 9x-13=.31 |